Learning Video Based on a Contextual Approach to Improve Metacognitive Skills in Grade III Elementary School English - Steffie Grace Lumbantobing; I Nyoman Jampel; Alexander Hamonangan Simamora (Universitas Pendidikan Ganesha, 2025)
Learning in elementary schools needs to emphasize metacognitive skills because these skills serve as a crucial foundation for shaping students' reflective and independent thinking. Metacognition involves the ability to understand and manage one's own thinking processes, such as planning, monitoring, and evaluating how one learns. However, in practice, the metacognitive skills of third-grade elementary students in English learning are still relatively low. This study aims to develop contextual-based instructional videos to improve the metacognitive skills of third-grade students in English subjects. This research is a type of Research and Development (R&D) using the Hannafin and Peck model, which consists of three stages: needs analysis, design, and development-implementation. The individual trial involved 3 students, the small group trial involved 9 students, and the field trial was conducted on a full class consisting of 30 students. The product was developed in the form of a learning video on the topic